A study of growth pattern of school going children of Kolkata, India - Ghorai, Tamal; Mazumder, Sahan; Gangopadhyay, Somnath; Chatterjee, Tapomoy; Shaw, Kartik; Das, Payel; Samanta, Amalendu (International Journal Of Community Medicine And Public Health, 2023)
Background: In our society only, a few peoples have good physiological status from their childhood. Health status of children and adolescents is important factor for young society. This present study highlights the peoples’ state of health and nutrition. Change in height with respect to age can be seen during puberty and adolescence. Growth can also be dependent upon the geographical regions. Methods: In this study included 230 adolescent students (boys- 146, girls- 84) in the age group of between 12-18 years. So many related growth parameters were measured using by an anthropometric rod, weighing machine, and slide calliper. BMI, p value was obtained by performing t-test at 0.05 level of significance. Statistical software SPSS version 20 was used. Results: Growth parameter was found to be increasing with age and it was more pronounced between 16 and 17 years. Interestingly the increment of all the growth parameter was found to be more in urban and less in rural. Conclusions: The findings of this study showed a progressively increasing of growth-related parameters with ages and the progress vary, indicating a nutritional supplementation are unequal (unequal growth pattern), as it was evident from different growth parameters percentile values of CDC and IAP values. This study will certainly help to create among the children and their parents about the physical growth and health.